Existing Calf Management and Milk Marketing Practices followed in Kheda and Panchmahal Districts of Middle Gujarat - Divekar, B.S.; Trivedi , M.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was undertaken in Kheda and Panchmahal districts of middle Gujarat to know the existing calf management and milk marketing practices followed by the dairy farmers. The study was conducted in randomly selected four talukas each from Kheda and Panchmahal districts. From each taluka five villages and from each village five respondents were randomly selected. Thus, total 200 respondents were included in the study. Majority (71.50 %) of the respondents followed practice of cutting the naval cord of the calf at the time of birth, of which 67.83 percent farmers were ligating and applying antiseptic to naval cord. More than half of the farmers followed disbudding in Kheda district whereas, more than three fourth of the farmers have not adopted this practice in Panchmahal district. Majority (95.00 %) of the respondents followed suckling / natural system of calf raising. Majority of the respondents provided colostrum to the calves within one hour of birth (55.00 %) or at the most between one to three hours of birth (28.50 %). Moreover, 38.00 percent of the farmers provided colostrums only after expulsion of placenta. Cent percent of the respondents from both the districts sold the milk to the dairy co-operative societies. However, majority (85.50 %) of the dairy farmers retained 1 to 2 liters of milk for their household consumption.